Jews and the state : dangerous alliances and the perils of privilege - Mendelsohn, Ezra (Studies in contemporary Jewry, 2003)
Bringing together contributions from established scholars from multiple disciplines and countries, Volume XIX of Studies in Contemporary Jewry offers a comparative view of alliances between Jewish communities and the state. Together, the volume's contents show the price Jews paid for allying with unpopular regimes. The essays cover the American South, South Africa, Canada, Algeria, Morocco, Poland, Hungary, Romania, and Russia.